Evaluation of Ratoon Potential and Yield of Some Sorghum Varieties (Sorghum bicolor L) - Akhmad Zubaidi; Dwi Ratna Anugrahwati; Baiq Erna Listiana; Novita Hidayatun Nufus; Anjar Azhari Pranggawan (Postgraduate, University of Mataram, 2024)
Sorghum production needs to be increased to meet food or feed needs because sorghum grain has nutritional qualities that are comparable to other grains such as corn. One of the advantages of the sorghum plant is the growth of new shoots from the base of the harvested stem which produces new plants, ratoon, that grow until they can be harvested. This experiment examines the ratoon potential of 5 sorghum varieties, Bioguma, Samurai, Pahat, Suri4, and the local Gando Keta variety so that we can utilize ratoon technology on these sorghum varieties. The experiment was carried out in a greenhouse using a Completely Randomized Design. It can be confirmed from this experiment that the dry matter weight of the main plants is higher compared to the ratoon plants' dry matter weight, however, the yield of the ratoon was higher than that of the main plants. Seed size contributes to the higher yield of the ratoon plants. Among all the varieties tested, Suri4 and Pahat show the best ratoon potential. Gando Keta, the local variety, has the lowest grain yield of main and ratoon compared to the other varieties.